A Novel Carbon Support: Few‐Layered Graphdiyne‐Decorated Carbon Nanotubes Capture Metal Clusters as Effective Metal‐Supported Catalysts. Issue 12 (3rd March 2021) - Lv, Yan; Wu, Xueyan; Lin, He; Li, Jiaxin; Zhang, Hongbo; Guo, Jixi; Jia, Dianzeng; Zhang, Hongmei
Abstract: Carbon‐supported metal nanocatalysts have received substantial attention for heterogeneous catalysis in industry. Hunting for suitable and impactful carbon supports that have strong interactions with metal nanocatalyst is a matter of great urgency. Herein, a well‐designed graphdiyne layer decorated on the carbon nanotubes sidewalls (CNT@GDY) serves as a novel carbon support. This unique hybrid structure effectively traps platinum and palladium atomic clusters (Pt/Pd‐ACs) with dimensions of 0.65 nm and 1.05 nm uniformly and firmly, forming novel carbon‐supported metal nanocatalysts (Pt(Pd)‐ACs/CNT @ GDY) for efficient hydrogen generation and aromatic nitroreduction, respectively. The Pt‐ACs/CNT@GDY can deliver an HER current density of 10 mA cm −2 with a small overpotential of 23 mV in 0.5 M H2 SO4, showing a greatly enhanced mass activity, intrinsic activity than the commercial Pt/C catalyst. The Pd‐ACs/CNT@GDY also exhibits excellent catalytic activity and a high turnover frequency of 38.0 min −1 for aromatic nitroreduction. The carbon support turns out to possess excellent conductivity, abundant and uniform reactive sites, low redox potential, more negative surface and large specific surface area as well as a strong interaction with ACs, as anticipated in ideal supports, which can be applied in other metal‐supported catalysts. Abstract : A novel carbon support (CNT@GDY) with few‐layer graphdiyne wrapped on the carbon nanotubes is constructed. The support has excellent electrical conductivity, abundant and uniform reaction sites, and strong interactions with the metal phase. Depositing Pt(Pd)‐ACs on the support via an electroless deposition method can serve as highly efficient heterojunction catalysts (Pt(Pd)‐ACs/CNT @ GDY).